Cellular proteome datasets of human endothelial cells under physiologic state and after treatment with caffeine and epigallocatechin-3-gallate - Chanthick, Chanettee; Thongboonkerd, Visith (Data in brief, 2019)
Human endothelial cells play several significant roles in vascular biology and homeostasis. We report herein cellular proteome datasets of EA.hy926 human endothelial cells under physiologic condition and after treatment with 100 μM caffeine or EGCG for 24-h. Cellular proteins were extracted and subjected to in-solution tryptic digestion using filter-aided sample preparation (FASP) method. The digested peptides were analyzed by nanoflow liquid chromatography coupled to tandem mass spectrometry (nanoLC-ESI-Qq-TOF MS/MS). Finally, the mass spectral data were searched against the human Swiss-Prot database using Mascot 2.4 search engine and quantified using Skyline v.3.5 software and BiblioSpec algorithm. All of these data were used for further comparative proteomics study followed by bioinformatics analyses to investigate differential biochemical effects of caffeine and EGCG on human endothelial cells (Chanthick et al., 2019) [1].